Ensino da leitura : como as letras são introduzidas no livro didático porta aberta - 1º ano - Araújo, Cristiane Menezes de (2017)
The present dissertation brings reflections on the initial teaching and learning of reading for literacy and citizenship, taking as object of investigation the textbook: Porta Aberta: letramento e alfabetização – 1º. Ano, da Ed. FTD, de Carpaneda & Bragança (2011), commonly adopted in public schools in Aracaju / SE. It aims to analyze the way how this book introduces the vowel and consonantal letters, in the light of the theoretical-methodological assumptions of the Scliar System of Literacy, considering (or not) the order of increasing complexity in the introduction of graphemes for the initial learning of the reading, such as the simplicity of the traces that make up the letters and their articulation; listening for the realization of the most perceptible phonemes by the learner, represented by the respective grapheme; the biunivocity relationship of each one of them; the graphemes that represent phonemes without variants determined by the phonetic context, among other complexities, as well as if the letters are (or aren't) presented by their names or the value that they represent. The theoretical-methodological foundations are firmly established in the works of Scliar-Cabral (2016; 2014; 2013b; 2007; 2003), whose purposes serve teaching practices aligned with the advanced discoveries of neuroscience, psycholinguistics, linguistics and the science concern to education, with emphasis on teaching strategies that highlight the importance of recognizing the graphic traits that identify the letters and the phonemic and phonological awareness in this initial phase of literacy. We know that, although the teaching of reading is compulsory in schools, the central focus for the development of this educational process is always more focused on the mechanical writing of letters, which imply the detriment of the effective learning process: there it is the causes of low reading and writing performance, according to the results presented in various National Assessments (ANA, 2015). We understand that unfortunately, even facing such a low reading performance of our children, the school still ends up silencing these questions, by not proposing an initial reading learning with more criticism, reflection and investment in the continued education of literacy teachers. It opts, then, for the reproduction of outdated approaches that, admittedly, present terrible results in national and international evaluations, starting with textbooks, sometimes they are not recommended by psycholinguistics scholars and related sciences that turn to the promising teaching of that specific ability, as evidenced in this study. The results of the work show that the methodology adopted in the textbook Porta Aberta: letramento e alfabetização – 1º. ano contrary to the advances already achieved for a scientifically based literacy by presenting the letters through nomination and according to the order of the alphabet and not according to the complexity of articulation of the traits that make them up, elencada in this study, and by introducing the vowel letters without interacting with the consonants. Finally, we believe that a process of the initial learning of reading for the exercise of citizenship passes through the automation of the recognition of: 1º - what are, how many are and how the traces that form the letters are combined; 2º what are the graphemes of written Brazilian Portuguese and the respective values (phonemes) that they represent (phonemic awareness); 3º - where the graphic accent of greater intensity goes in the stressed words and identification of the most frequent unstressed words, like articles and the coordinating conjunction "and", which allows the fast and fluent reading, to achive the textual understanding.